The Radio Frequency Identification Implementation Design for INLISLite Library Management System - Majidah, Majidah; Widiyanto, Widiyanto; Purwinarko, Aji; Harto, Kasinyo; Fridiyanto, Fridiyanto; Mukminin, Amirul (Malikussaleh University, Aceh, Indonesia, 2025)
A challenge with self-borrowing services is the investment cost for both software and hardware. A software license is required to connect INLIS [Integrated Library System] Lite with Radio Frequency Identification [RFID], which results in a high cost, especially when the software is only compatible with specific RFID devices. This study aims to look at the INLISLite Library Information System, focusing on implementing a self-borrowing service using microcontrollers and RFID technology. In this research, system development uses the prototyping method. This study developed a self-borrowing module for INLISLite without the need for licensed connector software. Additionally, the module is compatible with various microcontrollers and RFID devices that are readily available. The research proposes a novel model that utilizes RFID technology and NodeMCU ESP8266 for the INLISLite Library Information System. RFID sensors read book data from tags, while the NodeMCU microcontroller facilitates communication between the RFID system and the server, allowing automatic transmission of book data to the INLISLite database. This setup enables seamless self-service borrowing, which was tested successfully, supporting processes such as logging in, scanning book data, and updating loan status in the database.